Konsep, Karakteristik dan Wilayah (Scope) Kajian Manajemen Kurikulum Bahasa Arab - Muhammad Anwar (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2018)
Management of Arabic language curriculum that entered the realm of Islamic education management. Various objects of Arabic language education can be used as material which is then integrated to realize the education management characteristic of IslamArabic language curriculum covers the field of planning and development, implementation, and improvement of the curriculum. The main points of this activity can also be said as the scope of curriculum management. So the area of Arabic curriculum management scope is also the same, ie Arabic curriculum planning, Arabic curriculum execution, and improvement of Arabic language curriculum. Arabic curriculum management of its elements is; Person (Man), Cost (Money), Methode (Method), Material (Material).